PELATIHAN PEMBUATAN BAHAN AJAR UNTUK PEMBELAJARAN DARING MENGGUNAKAN APLIKASI VIDEO EDITING BAGI GURU DAN CALON GURU - Munawaroh Munawaroh; Widya Parimita; Ryna Parlyna; Santi Susanti; Ati Sumiati; Sri Zulaihati (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
The training is part of the community service activities of the lecturers of the Faculty of Economics, Universitas Negeri Jakarta. This Workshop is to educate and train teachers or prospective teachers to make teaching materials that are certainly interesting for students. Given the current COVID-19 pandemic, where everyone is encouraged to work or distance learning, all teachers must also teach students remotely. In addition, this training is also to prepare teachers to continue to adapt to the times because it is possible that learning and teaching activities will be carried out online and offline in the future.